CIMORY DAIRY LAND PRIGEN TOURIST DESTINATION WITH LEISURE PARK CONCEPT IN CATTLE FARMING IN PASURUAN - Hadi, Bawa Mulyono (Transpublika Publisher, 2024)
Cimory Dairy Land Prigen, located in Pasuruan Regency, East Java, carries the concept of a leisure park with a focus on cattle farming. This concept attracts various groups, ranging from families to tourists who are interested in the milk production process and farm life. This study aims to examine the application of the leisure park concept in Cimory Dairy Land Prigen, as well as its impact on visitor education and the local economy. This research also aims to identify development strategies that can increase the attractiveness and benefits of this destination. This research used a descriptive qualitative approach with data collection methods through in-depth interviews, direct observation, and document analysis. Interviews were conducted with managers, staff, and visitors, while observations were made to understand visitor interactions with existing facilities. Data were analyzed through reduction, presentation, and conclusion drawing to provide a comprehensive picture of the implementation of the leisure park concept in Cimory Dairy Land Prigen. The results showed that Cimory Dairy Land Prigen successfully implemented the leisure park concept well. This destination offers various educational and recreational activities such as farm tours, milking, and interaction with farm animals. Adequate infrastructure and supporting facilities such as restaurants and souvenir shops add to the convenience of visitors. The positive impact on the local economy is also evident from the support for micro, small and medium enterprises around the tourism area.